The Influence of Organizational Commitment on Employee Performance in Working Students - Septiani, Diah Ayu; Kristanto, Yudi; Taryanto, Taryanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to determine the effect of organizational commitment on employee work performance among Working Students. The research method used is a quantitative method. Data was collected using a survey method, using a questionnaire. The sample taken consisted of 66 respondents. The results of these measurements showed that statistical calculations obtained a correlation coefficient of r = 0.514 and a coefficient of determination of R = r2 = 0.265. Testing the significance of the correlation obtained tcount (4,800) > t table (1,670) ata = 0.05, this shows that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between Organizational Commitment and Employee Performance can be accepted. This means that the higher the Organizational Commitment, the higher the Employee Performance will be.